Combination treatment with anti-HER2 therapeutic antibody RC48, PD-1 inhibitor, radiotherapy, and granulocyte macrophage-colony stimulating factor (GM-CSF) in patient with metastatic gastric cancer: a case report - Liu, Zhuixing; Wang, Fang; Zhang, Yingqi; Lu, Jun; Yang, Yang (Frontiers in Immunology, 2024)
HER2 overexpression/amplification is a prevalent driver in various types of cancer, including gastric cancer (GC). Limited options are available for patients with HER2-positive metastatic gastric cancer, particularly those who do not respond to the standard therapy of HER2 antibody trastuzumab combined with chemotherapy. Previous research suggests that combining a PD-1 inhibitor with radiotherapy and granulocyte macrophage-colony stimulating factor (PRaG regimen) may enhance the antitumor effects in patients with chemotherapy-resistant metastatic solid tumors. In this case study, we presented a potential treatment strategy of a patient having HER2-positive and PD-L1-negative gastric adenocarcinoma. The patient showed rapid tumor progression even after surgery and multiple trastuzumab plus chemotherapy treatments. To address this, we employed a novel anti-HER2 antibody called RC48 in combination with PRaG regimen therapy (PRaG3.0). The patient demonstrated a positive response after two treatment cycles and achieved a progression-free survival time of 6.5 months. This case highlights the potential of four-combination therapies for treating refractory, multiorgan, HER2-positive, PD-L1-negative metastatic gastric cancer. Additionally, varying radiation doses in targeting dual foci is critical to enhance tumor immunotherapy.